Two-step catalytic reactive extraction and transesterification process via ultrasonic irradiation for biodiesel production from solid Jatropha oil seeds - Tan, Shiou Xuan; Lim, Steven; Ong, Hwai Chyuan; Pang, Yean Ling; Fitranto, Kusumo; Goh, Brandon Han Hoe; Chong, Cheng Tung (Elsevier, 2019)
A two-step catalytic reactive extraction and transesterification process was adopted to synthesize biodiesel from solid Jatropha seeds, a non-edible source with high free acid content, directly using ultrasound irradiation. From the intensification of reactive extraction process coupled with ultrasound, esterified oil with satisfactory extraction efficiency of 84.0 ± 0.5%, FAME purity of 38.6 ± 1.3% and esterification efficiency of 71.1 ± 1.3% were obtained. High acid value (AV) of 18.2 ± 0.5 mg KOH/g was successfully reduced to 5.3 ± 0.2 mg KOH/g. In the subsequent transesterification of esterified Jatropha oil, FAME purity of 99.0 ± 1.3% and biodiesel yield of 85.2 ± 1.3% were attained at KOH loading of 1.5 wt.%, methanol to oil molar ratio of 12:1 and ultrasonic amplitude of 60% after 15 min reaction time. From the artificial neural network (ANN) modelling, coefficient of determination (R2) for FAME purity and biodiesel yield were found to be 0.9926 and 0.9845, respectively, which proved that the model had good fit with the experimental data. Under the same optimized reaction conditions, this process intensification could achieve higher FAME purity (99.0% vs. 91.8%), biodiesel yield (85.2% vs. 75.6%) and AV reduction efficiency (88.5% vs. 88.2%) than conventional magnetic stirring. © 2019 Elsevier B.V.